Impact of sleep quality on body weight status during the COVID-19 pandemic among Malaysian adults - Ying, C.Y.; Yokanantini, Muniandy; Anis Syazwina, Salman; Farah Wahidah, Awi; Nur Zahirah, Abd Samad (2021)
Objective COVID-19 is a new emerging situation that has dramatically impacted both individuals and society on their sleep quality and body weight status. This study aimed to determine the association between sleep quality and body weight status in Malaysian adults during the COVID-19 pandemic. Methodology The study design was cross-sectional, where all participants filled the bilingual Google Form questionnaire, distributed through social media. The present study was conducted using a convenience sampling method in Malaysia, including Peninsular Malaysia, Sabah, and Sarawak. A total of 705 Malaysian adults between ages 18 to 59 were recruited. Sleep quality was assessed by Pittsburgh Sleep Quality Index (PSQI). Self-administered socio-demographic, height and weight for BMI were obtained. Pearson correlation test were conducted to measure the association between sleep quality and body weight status using IBM SPSS Statistics for Windows version 22.0. Results & Discussion A total of 80.7% of them were females while males were 19.3%. The mean age of the participants is 30.0 (11.0). Findings revealed that 14.3% of Malaysian adults had good sleep quality and 85.7% of them with poor sleep quality. The mean height, weight and body mass index of the participants were 159.7 (8.3) cm, 63.4 (16.4) kg, and 24.9 (6.3) kg/m2 respectively. A total of 8.8% of them were underweight, followed by 50.9% of normal BMI, 19.6% of overweight, and 20.7% of obese. The study showed there was a significant, positive and poor correlation between sleep quality and body weight status (r=0.076, p=0.042). Conclusion Findings suggested that poor sleep quality causes higher BMI. Future research on factors affecting sleep quality is necessary to improve adult's sleep quality especially the world is in new age of technology. Thus, it provides opportunity for healthcare professionals in promoting healthy weight management during the pandemic of COVID-19.